The Effect of Annealing Temperature Growth on Fe-TiO2 Thin Film Photoactivity in Methylene Blue - Kaltsum, Ummi; Permatasari, Ema Chintya; Murniati, Ngurah Ayu Nyoman; Kurniawan, Wawan; Saefan, Joko (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2019)
The purpose of this study is to determine the effect of annealing temperature growth on Fe-TiO2 thin film photoactivity. This was made by mixing TTIP, AcAc, ethanol, and Iron Nitrate Nanohydrate, after which the obtained mixture was sprayed and annealed on the substrate for two hours using the coating method. The temperature was increased to 500°C, 550°C, and 600°C, with the thin film photoactivity determined in methylene blue using UV light for 5 hours with decreasing values of COD, BOD, and absorbance. The results show annealing temperature growth increased photoactivity of the thin film. The highest photoactivity at 600°C in degrading methylene blue with decreasing values of COD, BOD, and absorbance was 19.56%, 35.84%, and 66.70%, respectively.